STRATEGI GURU PAI UNTUK MENINGKATKAN MINAT BELAJAR DI MTSN 10 TABALONG - Hatmiah Hatmiah (CV. ADIBA ASIHA AMIRA, 2023)
The PAI teacher's strategy to increase interest in learning is highly expected, because it really helps students in mastering teaching materials. Based on this statement, the formulation of the problem in this study was carried out, namely what is the PAI teacher's strategy to increase interest in learning at MTsN 10 Tabalong? and what are the factors that influence it?. The purpose of this study was to find out the strategies of PAI teachers to increase their interest in learning at MTsN 10 Tabalong and to find out the factors that influence them. The subjects in this study were one PAI teacher and several students at MTsN 10 Tabalong. The techniques used in data collection are interviews, observations, and documentaries. Then processed through the process of data reduction, data display, and data verification. Meanwhile, to analyze the data the author uses descriptive and qualitative analysis. After the data has been analyzed, it can finally be concluded that 1) The PAI teacher's strategy to increase interest in learning at MTsN 10 Tabalong, namely a) In this cooperative strategy, the PAI teacher has made groups and made rules in groups and the rules are intended to be active in expressing their opinions or the sound. b) In this inquiry strategy, PAI teachers often do this by giving assignments to students, both personal assignments and group assignments. In the process, PAI teachers place great emphasis on student understanding. c) In this expository strategy, PAI teachers place more emphasis on students' understanding of the material they are studying. d) In this asking strategy, students can ask PAI teachers and students can also ask fellow students. 2) Factors that influence it, such as a) Factors from within students show that all students are physically healthy and students also do not experience physical disabilities. So for the factors that exist in these students there is no problem. b) Factors that are outside of these students, such as the friend factor that makes learning enthusiastic. The factor of parents who are busy with work makes their children's learning outcomes decrease.